Developing Positive Education Integrated Extensive Reading Materials for EFL Students - Andini Linarsih (Jurnal Pendidikan Bahasa, 2020)
Positive education for students has an impact on improving wellbeing. The cultivation of positive educational values can be integrated into all learning activities, especially reading activities. This study aims to make the extensive reading text as supplementary material in English courses that contain positive educational values for the readers. It is hoped that after reading the text in this book, the readers will not only improve their English skills but also have a psychological effect that can motivate students to love learning and be persistent in learning in general, learning English in particular. Primary data obtained in this study were obtained directly from respondents, in the form of exploratory results carried out in preliminary studies carried out through discussions with experts related to content and language, as well as data on limited trial results on 1st-semester students at a university in Pontianak. The data collection instrument was a questionnaire instrument. This study uses the Research and Development approach developed by Doolitle (2015). The results of the validation from the content validator, the language validator, and the students showed that the book was suitable for use even though it had to go through several revisions.